2015
DOI: 10.1007/s10853-015-9358-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure, composition, and defect control during plasma spray deposition of ytterbium silicate coatings

Abstract: Environmental barrier coatings (EBCs) are needed to protect SiC structures exposed to high temperatures in water vapor-rich environments. Recent studies of a tri-layer EBC system consisting of a silicon layer attached to the SiC, a mullite diffusion barrier and a lowsteam volatility ytterbium silicate topcoat have shown some promise for use at temperatures up to 1316°C. However, the performance of the coating system appeared to be dependent upon the manner of its deposition. Here, an air plasma spray method ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(78 citation statements)
references
References 70 publications
2
75
0
1
Order By: Relevance
“…Therefore, silicon preferentially evaporates from the over‐heated Yb 2 SiO 5 particles during the spray process, which results the layer microstructure with significant color variation in the as‐sprayed coating. Different deposition parameters have effects on composition of the as‐deposited splats and orientation of microcracking in Yb 2 SiO 5 layer . Modification of deposition parameters might be an effective way to depressing the decomposition of Yb 2 SiO 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, silicon preferentially evaporates from the over‐heated Yb 2 SiO 5 particles during the spray process, which results the layer microstructure with significant color variation in the as‐sprayed coating. Different deposition parameters have effects on composition of the as‐deposited splats and orientation of microcracking in Yb 2 SiO 5 layer . Modification of deposition parameters might be an effective way to depressing the decomposition of Yb 2 SiO 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, plasma spray is a quite direct method for coating deposition that imparts high temperatures to the feedstock particles, which is suitable for the preparation of coatings with high melting points. As for Yb 2 SiO 5 coating, a tri‐layer Yb 2 SiO 5 /Al 6 Si 2 O 13 /Si system has been deposited onto SiC substrates using APS approach . It is found that both penetrated and randomly oriented microcracks formed in the Yb 2 SiO 5 layer on silicon and mullite‐coated SiC substrates because of the higher CTE of Yb 2 SiO 5 compared to that of the substrate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These layers are often fabricated by coating method such as air plasma spraying (APS) . However, cracks can be generated during the deposition process of APS, and then during thermal cycling of the EBC. These cracks can lead to the failure of EBC during operation .…”
Section: Introductionmentioning
confidence: 99%
“…The Cahn Prize for 2016 will be presented to Bradley Richards, Hengbei Zhao and Haydn Wadley at the Cahn Prize Dinner in Boston at the end of MRS week. Their paper entitled ''Structure, composition, and defect control during plasma spray deposition of ytterbium silicate coatings'' appeared in the December 2015 issue [3]. If you get a chance to look at this paper, you will notice that it was submitted on June 25, 2015, accepted on August 14, 2015, and appeared online on September 15, 2015.…”
mentioning
confidence: 99%